Liver Transplantation: Historical Aspects - Cunha, André Gusmão; Bastos, Jorge Luiz Andrade; Meyer-Nascimento, Roberto José (Brazilian Journal of Transplantation, 2013)
Little more than half a century has passed since the pioneering works on experimental liver transplantation. Currently, orthotopic liver transplantation is the treatment of choice for various acute and chronic liver diseases, which endanger life or cause significant deterioration of the quality of life of patients that are not curable with other treatments. In half a century, the therapy for liver transplantation has evolved with multiple stages of development and affirmation.